An Experimental Study on the Security Performance of YASS - Huang, Fangjun; Huang, Jiwu; Shi, Yun Qing (IEEE transactions on information forensics and security, 2010)
This paper presents an experimental study on the security performance of Yet Another Steganographic Scheme (YASS). It reports: 1) YASS's security performance with different input images, i.e., uncompressed images and JPEG compressed images; 2) YASS's security performance compared with two other JPEG steganographic schemes MB1 and F5; and 3) some experimental results about extended YASS.